The Influence of Knowledge, Motivation, and Support and Facilities on the Interest of Teachers of SMP Negeri 8 Jayapura in Publishing Publications: A Quantitative Approach to Identifying Constraints and Solutions - Virman, Virman (Lembaga Penerbitan dan Publikasi Ilmiah Program Pascasarjana IAI Sunan Giri Ponorogo, 2025)
This study aims to identify the factors that affect the interest of SMP Negeri 8 Jayapura teachers in publishing scientific publications, analyze the obstacles faced, and offer solutions based on quantitative approaches. All population members were used as respondents in this saturated sample study, which involved 75 instructors at SMP Negeri 8 Jayapura. A 5-point Likert scale was used in the questionnaire used to collect the data. Evaluation of the measurement model, structural model, and hypothesis testing were all part of the data analysis process utilizing Smart PLS 4. The study identified three main variables that influenced teachers' scientific publications, namely knowledge of scientific writing techniques (X1), writing Motivation (X2), and access to facilities and support (X3). All three significantly affected scientific publications (Y), with the most significant contribution from knowledge (loading 0.922). Cronbach's Alpha scores of 0.783–0.827 and Composite Reliability > 0.827 indicated encouraging validity and reliability testing findings. Hypothesis testing showed that X1, X2, and X3 had a significant positive effect on Y, confirming the importance of increasing knowledge, Motivation, and support to improve teachers' scientific publications.